2004
DOI: 10.1152/ajpgi.00396.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of the human GLUT7 isoform SLC2A7 from the small intestine

Abstract: Facilitated glucose transporters (GLUTs) mediate transport of sugars across cell membranes by using the chemical gradient of sugars as the driving force. Improved cloning techniques and database analyses have expanded this family of proteins to a total of 14 putative members. In this work a novel hexose transporter isoform, GLUT7, has been cloned from a human intestinal cDNA library by using a PCR-based strategy (GenBank accession no. AY571960). The encoded protein is comprised of 524 amino acid residues and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 34 publications
(32 reference statements)
3
88
0
1
Order By: Relevance
“…22,26,27,30 A major difference between Class I and II is that Class II lacks the tryptophan residue after the GPXXXP motif. 58 Another striking difference is that all Class II GLUTs have a single hydrophobic residue, isoleucine, in TM7 associated with fructose/glucose selectivity.…”
Section: Class II Glutsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,26,27,30 A major difference between Class I and II is that Class II lacks the tryptophan residue after the GPXXXP motif. 58 Another striking difference is that all Class II GLUTs have a single hydrophobic residue, isoleucine, in TM7 associated with fructose/glucose selectivity.…”
Section: Class II Glutsmentioning
confidence: 99%
“…25 In 2004, human GLUT7 was the last member of the GLUTs to be cloned using an intestinal cDNA and a polymerase chain reaction-based strategy. 26 Having 528 amino acids, GLUT7 shares 68% similarity and 53% identity with GLUT5 and is predominantly expressed at the apical membrane of the enterocytes in the small intestine. This GLUT can transport both glucose and fructose when expressed in Xenopus oocytes with high affinity, but with very low transport capacity, and it is not sensitive to cytochalasin B.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GLUT5, GLUT7, GLUT9, and GLUT11 are all members of class II of the GLUT family, grouped together because of their high degree of amino acid identity (40 -60%) and deduced to have fructose transport activity because of their similarity to GLUT5 (16). GLUT7 (17,18) and GLUT9 (19) subsequently have been confirmed to have fructose-inhibitable glucose uptake. In addition, GLUT8 and GLUT12 have been shown to transport both glucose and fructose (20).…”
Section: Impact Of the 8-week Protocol On Glycemic Controlmentioning
confidence: 99%
“…In the testis of the male reproductive tract, predominant expression of Slc2a8 has been demonstrated by Chen et al (2003) and Zhao et al (2004). Others have also shown that Slc2a1, Slc2a5, and Slc2a7 are localized in the testis Davidson et al, 1992;Li et al, 2004;Ulisse et al, 1992). Even though Schürmann et al (2002) have shown the presence of GLUT8 at the acrosomal region of mature spermatozoa within the epididymis, the expression of other Slc2a isoforms in the epididymis has not been determined in detail.…”
Section: Introductionmentioning
confidence: 99%